s=t3−3t2−9t+2s′=3t2−6t−9s^{"}=6t-6a) Vận tốc khi t=2 là s^{'}(2)=3.2^{2}-6.2-9=-9 (m/s)
b) Gia tốc khi t=3 là s^{"}(3)=6.3-6=12 (m/s^{2})
c) Vận tốc triệt tiêu \Leftrightarrow s^{'}=0 \Leftrightarrow 3t^{2}-6t-9=0
\Leftrightarrow \left[ \begin{array}{l}t=-1 (L)\\t = 3\end{array} \right.
\Leftrightarrow t=3
Gia tốc tại thời điểm vận tốc triệt tiêu là
s^{"}(3)=6.3-6=12 (m/s^{2})
d) Gia tốc triệt tiêu \Leftrightarrow s^{"}=0\Leftrightarrow 6t-6=0\Leftrightarrow t=1
Vận tốc tại thời điểm gia tốc triệt tiêu là
s^{'}(1)=3.1^{2}-6.1-9=-12 (m/s)